Analisis Pengaruh Kinerja Perangkat Desa terhadap Pelayanan Di Kantor Desa Kehidupan Baru Kecamatan Maro Sebo Ilir Kabupaten Batang Hari - Etty Siswati; Afriantoni Afriantoni; Niki Kosasi; Linda Sari (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The purposes of this study and this research are 1. To determine the effect of the quality of work of village officials on services, 2. To determine the effect of the work quantity of village officials on services, 3. To determine the effect of Timeliness of village officials on services, 4. To determine the effect of the effectiveness of village apparatus village to service, 5. To find out the effect of work independence of village apparatus on service. 6. To determine the effect of work quality, work quantity, punctuality, effectiveness, work independence on services in the office Desa Kehidupan Baru Kecamatan Maro Sebo Ilir Kabupaten Batang Hari. Quantitative descriptive research methods and qualitative data collection methods using interviews, observations and questionnaires with a sample of 60 respondents and data analysis tools using a Likert scale. Research Results 1. Work Quality Variables ttable value 1.67303 and tcount 0.214 have no effect on service in the office Desa Kehidupan Baru Kecamatan Maro Sebo Ilir Kabupaten Batang Hari.2. Variable Quantity (X2) ttable value 1.67303 and tcount 0.052 has no effect on Service in the Office Desa Kehidupan Baru Kecamatan Maro Sebo Ilir Kabupaten Batang Hari. 3. Variable Punctuality (X3) ttable 1.67303 and tcount -0.033. Punctuality variable has no effect on Service in the Office Desa Kehidupan Baru Kecamatan Maro Sebo Ilir Kabupaten Batang Hari. 4. Effectiveness variable (X4) ttable 1.67303 and tcount 11.278. Effectiveness affects services in the office Desa Kehidupan Baru Kecamatan Maro Sebo Ilir Kabupaten Batang Hari. 5. Work independence variable (X5) ttable 1.67303 and tcount 12.843. Work Independence Variables affect Service in the Office Desa Kehidupan Baru Kecamatan Maro Sebo Ilir Kabupaten Batang Hari. Together (simultaneously) Fcount 1136.905 > 2.38 . This means that work quality, work quantity, punctuality, effectiveness, work independence have an influence on services in the office Desa Kehidupan Baru Kecamatan Maro Sebo Ilir Kabupaten Batang HariÂ